2008
DOI: 10.1002/j.2051-5545.2008.tb00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal process, suicidal communication and psychosocial situation of young suicide attempters in a rural Vietnamese community

Abstract: The study aimed to explore the suicidal process, suicidal communication and psychosocial situation of young suicide attempters in a rural community in Hanoi, Vietnam. Semi-structured interviews were conducted, in a community setting, with 19 suicide attempters aged 15-24 who had been consecutively hospitalized in an intensive care unit. In 12 of 19 cases, the first pressing, distinct and constant suicidal thoughts appeared less than one day before the suicide attempt in question. However, distress and mild, fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 25 publications
0
43
0
1
Order By: Relevance
“…Although some previous studies have asked about respondents’ intentions to assist a person at risk of suicide, this risk has always been overtly expressed, despite most suicide communications being indirect (Shand et al., ; Wasserman et al., ; Wolk‐Wasserman, ). Given the high number of community members exposed to close family members or friends at risk of suicide (Cerel et al., ; Maple et al., ), it is imperative to understand whether community members can recognize indirect signs of suicide risk and respond accordingly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some previous studies have asked about respondents’ intentions to assist a person at risk of suicide, this risk has always been overtly expressed, despite most suicide communications being indirect (Shand et al., ; Wasserman et al., ; Wolk‐Wasserman, ). Given the high number of community members exposed to close family members or friends at risk of suicide (Cerel et al., ; Maple et al., ), it is imperative to understand whether community members can recognize indirect signs of suicide risk and respond accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Between 58% and 85% of Australians know someone who has died by suicide, and about one‐third of these had a close relationship with that person (Maple et al., ). Between one‐third and one half of people who die by suicide (Isometsä, ), and a similar proportion who attempt suicide, communicate their suicidal intentions to loved ones (Paraschakis, Michopoulos, Christodoulou, Koutsaftis, & Douzenis, ; SANE Australia and University of New England, ; Wasserman et al., ; Wolk‐Wasserman, ). However, family members and friends can find it difficult to recognize suicide risk or may not know how to respond when a person close to them expresses their suicidal thoughts (Owen et al., ; Owens et al., , ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that there is marked diurnal variation with regards to parasuicide, with an evening peak for nonviolent episodes [21]. In the study context, the time of the day did not make a difference to parasuicide as evidenced by almost equal distribution of times of day for parasuicide.…”
Section: Time Of the Day When Parasuicide Occurredmentioning
confidence: 61%
“…Communication of intent is recognized as an important signal of suicide risk (Suominen, Isometsä, Henriksson, Ostamo, & Lönnqvist, 1997); however, the meaning and impact of this communication may differ across social‐cultural contexts (Eskin, 2003; Wasserman et al., 2008). A better identification and understanding of any signs of intent would be desirable, owing to the potential implications this may have in preventing suicidal behaviors.…”
mentioning
confidence: 99%